Molecular Systematics Of Cryptocoryne Spp. From Indo-Malaya Archipelago - Mohd Talkah, Nurul Shakina (2023)
Several expeditions in Sumatera and adjacent islands have resulted in identifications of new Cryptocoryne species and interspecific hybrids within the genus. Some of the newly discovered species possessed a mixture of morphological structure from different Cryptocoryne species. These newly described species were proven to exhibit various ploidy level even within nearby geographical area. The situation has resulted in taxonomic complexity of this genus. In this study, complete chloroplast genome reconstruction was done using next-generation sequencing (NGS) technology and perl programming language.